The Role of stressors in the prediction of procrastination and academic burnout among the Nursing Students of Ilam University of Medical Sciences in 2015 - Hamid Taghinegad; Arman Azadi; Homa Jamaledin; Milad Azizi (Kurdistan University of Medical Sciences, 2016)
Abstract Introdoction and Aim: This study was conducted to determine the role of stressors in the prediction of procrastination and academic burnout among the nursing students of Ilam University of Medical Sciences. Materials and Methods: This study descriptive – correlational study was conducted on 150 nursing students who were selected using random sampling method. The data collection tool consisted of studentship stressors, procrastination assessment scale and the academic burnout scale. Results: The results showed a significant positive correlation (p<0/5) among all components of stressors and its total score with procrastination and academic burnout dimensions and its total score. on the whole, the increase in each of the studentship stressors, including learning environment, educational condition, graduation and dormitories as well as all of them altogether led to the increase in the amount of procrastination, academic burnout and its dimensions including emotional exhaustion, apathy and educational inefficiency. Conclusion: The results showed that the studied variables are able to predict procrastination and academic burnout in students. As much as the scores of stressors related to educational condition, educational environment, graduation and dormitories were added, the scores of procrastination and academic burnout increased. Key words: stressors, procrastination, academic burnout, nursing students